2015
DOI: 10.13092/lo.71.1781
|View full text |Cite
|
Sign up to set email alerts
|

Focus Particles in Information Processing: An Experimental Study on Pragmatic Scales with Spanish incluso

Abstract: Focus particles have been one of the spotlights of linguistic research during the last fifty years. They have been studied mainly from a syntactic and semantic perspective, in formal and functional approaches. However, in the last years new insights in this field have been developed through pragmatic and textual approaches. From that perspective, focus particles can be considered as a type of discourse particles, as far as their semantic nature and their pragmatic function are concerned. In this paper, we clai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…also König 1991: 100). Furthermore, Loureda et al (2015) showed that processing a closed class of alternatives, ordered on a pragmatic, or evaluative scale, is less costly than processing an open class of alternatives, ordered on a pragmatic, or evaluative scale, and that the role of the focus particle differs with respect to the two different classes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…also König 1991: 100). Furthermore, Loureda et al (2015) showed that processing a closed class of alternatives, ordered on a pragmatic, or evaluative scale, is less costly than processing an open class of alternatives, ordered on a pragmatic, or evaluative scale, and that the role of the focus particle differs with respect to the two different classes.…”
Section: Discussionmentioning
confidence: 99%
“…Another resemblance can be found between bloß and the focus particle auch, with bloß discarding all the other elements of a set and auch indicating that the information conveyed by the sentence is valid for all elements of the set (cf. Loureda et al 2015). The processing steps for the different counterparts are not fundamentally different.…”
Section: Discussionmentioning
confidence: 99%
“…A contrastive focus (as opposed to an informative focus, that is, the focus that adds new information to the common ground by widening and expanding it [Escandell Vidal and Leonetti 2009: 15]) applies to the linguistic material "that the speaker calls to the addressee's attention, thereby o en evoking a contrast with other entities that might ll the same position" (Gundel and Fretheim 2005: 181). For an overview of other denominations, see Portolés 2010, Loureda et al 2015.…”
Section: Incluso 'Even' As An Additive Focus Operatormentioning
confidence: 99%